2020
DOI: 10.3389/fpsyg.2020.01554
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trust on Gaze-Mediated Attentional Orienting

Abstract: The last two decades have witnessed growing interest in the study of social cognition and its multiple facets, including trust. Interpersonal trust is generally understood as the belief that others are not likely to harm you. When meeting strangers, judgments of trustworthiness are mostly based on fast evaluation of facial appearance, unless information about past behavior is available. In the past decade, studies have tried to understand the complex relationship between trust and gaze-cueing of attention (GCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(116 reference statements)
2
3
0
Order By: Relevance
“…The results of our learning phase showed the counter-intuitive finding that response times to targets cued by informativevalid identities (i.e., they always cued the target) were similar to those cued by informative-invalid identities (i.e., they never cued the target). This sort of "counter-cuing" is consistent with previous research that has used similar learning paradigms (Joyce et al, 2016; but see Barbato et al, 2020) and has been suggested to occur because the encoding of the expected gaze behaviour interferes with and slows down the attentional response (see also Morgan et al, 2014). Additional research on the learning effects on gaze following has shown similar findings with, for example, identities that had previously consistently followed participants' gaze direction later being less effective as gaze cues than identities who never followed the participants' gaze (Dalmaso et al, 2015; see also Edwards et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our learning phase showed the counter-intuitive finding that response times to targets cued by informativevalid identities (i.e., they always cued the target) were similar to those cued by informative-invalid identities (i.e., they never cued the target). This sort of "counter-cuing" is consistent with previous research that has used similar learning paradigms (Joyce et al, 2016; but see Barbato et al, 2020) and has been suggested to occur because the encoding of the expected gaze behaviour interferes with and slows down the attentional response (see also Morgan et al, 2014). Additional research on the learning effects on gaze following has shown similar findings with, for example, identities that had previously consistently followed participants' gaze direction later being less effective as gaze cues than identities who never followed the participants' gaze (Dalmaso et al, 2015; see also Edwards et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Additional research on the learning effects on gaze following has shown similar findings with, for example, identities that had previously consistently followed participants' gaze direction later being less effective as gaze cues than identities who never followed the participants' gaze (Dalmaso et al, 2015; see also . These results converge to suggest that social learning has a complex relationship with subsequent social attentional responses (e.g., Dalmaso et al, 2015) and perceived value of social information (e.g., Barbato et al, 2020;Dalmaso et al, 2020). Importantly, however, our results…”
Section: Cue Numerosity and Social Informationsupporting
confidence: 79%
“…Thus, this study confirms that attentional shifts in the gaze cueing paradigm reflected a relatively automatic process, which was unaffected by social traits of faces. Recent reviews (Barbato et al, 2020; Dalmaso, Castelli, & Galfano, 2020) highlighted controversial results concerning social modulators of the gaze cueing effect, in particular when complex and multifactorial social constructs were explored, and suggested that the impact of social variables could depend on the relevance of such variables for the task or the observer (see also Ciardo et al, 2014; Ricciardelli et al, 2013). We can interpret our results as in line with this idea, since the experimental task of discriminating target letters did not induce the participants to consider trustworthiness and dominance of face stimuli as relevant features for the task itself.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent review on the effect of trust on gaze cueing of attention highlighted the contradictory results in the previous literature, pointing to methodological differences between studies related to features of the stimuli, trust manipulation, and sample characteristics. The review encouraged further research to unveil the relationship between social judgement and orienting of attention (Barbato et al, 2020). It is also important to consider the temporal dynamics of gaze cueing and of the possible impact of social variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation